The Role of Organizational Commitment and Organization Culture Toward Job Performance - Tuti Setyorini; Janri Delastriani Manafe; Indawati Jauhar Nino (Jur. Akuntansi, Politeknik Negeri Malang, 2022)
This study seeks to find out the factors that affect lecturers’ performance in Indonesia. Data were collected through a questionnaire participated by 178 active lecturers at the State Polytechnic of Kupang. The present study is important since it may give solutions to enhance the performance of Kupang State Polytechnic lecturers. Data analysis was conducted using the principles of Structural Equation Modeling (SEM). The results of this study demonstrated that there are direct and indirect influences of organizational culture and commitment toward lecturer performance as mediated by Organizational Citizenship Behavior (OCB). This shows the importance of OCB as a situational factor that can improve the performance of teaching staff in an educational institution.AbstrakPenelitian ini memiliki tujuan untuk menyelidiki faktor-faktor yang berpengaruh terhadap kinerja dosen di Indonesia. Pengumpulan data dilakukan dengan kuesioner dengan 178 dosen aktif Politeknik Negeri Kupang sebagai responden. Penelitian ini penting karena dapat memberikan solusi bagi peningkatan kinerja dosen di Politeknik Negeri Kupang. Data dianalisa dengan menggunakan Structural Equation Modeling (SEM). Secara langsung maupun tidak langsung terdapat pengaruh dari budaya dan komitmen organisasi terhadap kinerja dosen yang diperantarai oleh Organizational Citizenship Behavior (OCB). Penelitian ini mengetengahkan pentingnya OCB sebagai faktor situasional yang dapat meningkatkan kinerja tenaga pengajar di suatu lembaga pendidikan.